THE CRITICAL ROLE OF THE ADMISSIONS MANAGEMENT TEAM AND THE BOUNDARIES OF THEIR RESPONSIBILITIES (ІННОВАЦІЙНІ ПРОЦЕСИ ОСВІТНЬОЇ СФЕРИ УКРАЇНИ ТА КРАЇН ЦЕНТРАЛЬНОЇ ЄВРОПИ: СТАН, ПРОБЛЕМИ І ПЕРСПЕКТИВИ, 2024)
.